2012
DOI: 10.1016/j.physletb.2012.08.031
|View full text |Cite
|
Sign up to set email alerts
|

Significance of tension for gravitating masses in Kaluza–Klein models

Abstract: In this letter, we consider the six-dimensional Kaluza-Klein models with spherical compactification of the internal space. Here, we investigate the case of bare gravitating compact objects with the dustlike equation of statep 0 = 0 in the external (our) space and an arbitrary equation of statep 1 = Ωε in the internal space, whereε is the energy density of the source. This gravitating mass is spherically symmetric in the external space and uniformly smeared over the internal space. In the weak field approximati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…However, fluctuations of background matter concentrate around the gravitating mass and the bare gravitating mass gets covered by this coat to attain effective relativistic pressure in the external space. Certainly, this contradicts the observations (e.g., Sun does not have such relativistic pressure) and the only way to avoid such problem is to introduce, again, tension in the internal space [10,14].…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…However, fluctuations of background matter concentrate around the gravitating mass and the bare gravitating mass gets covered by this coat to attain effective relativistic pressure in the external space. Certainly, this contradicts the observations (e.g., Sun does not have such relativistic pressure) and the only way to avoid such problem is to introduce, again, tension in the internal space [10,14].…”
Section: Introductionmentioning
confidence: 91%
“…To get it we should put B 1 /A 1 = 1 [15]; this is our fine tuning condition. As it follows from (13) and (14), this takes place if δε + δp 0 + 2δp 1 +ρc 2 = 0 ,…”
Section: Background and Perturbed Modelsmentioning
confidence: 99%
“…Additionally, taking into account that h µν = 0 for µ ν and h µn = 0, we arrive at the conclusion that the perturbed metric retains the block-diagonal form. In our previous papers the block-diagonal form of the perturbed metric was accepted either as an ansatz [7] or as a consequence of the assumption of uniform smearing (over the internal space) of the gravitating mass [3,5,6]. In the present article, we demonstrate for the considered model that this statement follows directly from the Einstein equation and gauge condition without both of these assumptions.…”
Section: Weak-field Limit Of Black Strings and Black Branesmentioning
confidence: 55%
“…It is well known that compact nonrelativistic astrophysical objects such as our Sun have the dust-like EoS since the pressure inside them is much less than the energy density. In our paper [6] we have shown that in the case of multidimensional models the gravitating masses acquire effective relativistic pressure in the external space. Certainly, such pressure contradicts the observations.…”
Section: Weak-field Limit Of Black Strings and Black Branesmentioning
confidence: 81%
See 1 more Smart Citation